Effective three‐dimensional culture of hepatocyte‐like cells generated from human adipose‐derived mesenchymal stem cells. (10th August 2021) - Saito, Yu; Ikemoto, Tetsuya; Tokuda, Kazunori; Miyazaki, Katsuki; Yamada, Shinichiro; Imura, Satoru; Miyake, Masato; Morine, Yuji; Oyadomari, Seiichi; Shimada, Mitsuo
Abstract: Background: The aim of this study was to clarify the effectiveness of a new three‐dimensional (3D) culture system for hepatocyte‐like cells (HLCs) generated from human adipose‐derived mesenchymal stem cells (ADSCs). Methods: Human ADSCs (2 × 10 4 ) with or without 0.1 mg/mL human recombinant peptide μ‐piece per well were seeded in a 96‐well U‐bottom plate and then our three‐step differentiation protocol was applied for 21 days. At each step, cell morphology and gene expression were investigated. Mature hepatocyte functions were evaluated after HLC differentiation. These parameters were compared between 2D‐ and 3D‐cultured HLCs, and, DNA microarray analysis was also performed. Finally, HLCs were transplanted in to CCl4 induced acute liver failure model mice. Results: Two‐dimensional‐cultured HLCs at day 21 did not have a spindle shape and had formed spheroids after day 6, which gradually increased in size for 3D‐cultured HLCs. Definitive endoderm, hepatoblast, and hepatocyte genes showed significantly higher expression in the 3D culture group. Three‐dimensional‐cultured HLCs also had higher albumin expression, CYP3A4 activity, urea synthesis, and ammonium metabolism, and much higher expression of ion transporter, blood coagulation, and cell communication genes. HLC transplantation improved serum liver function, especially in T‐Bil levels, and engrafted into immunodeficient mice with HLA class I positive staining. Conclusion: Our new 3D culture protocol is effective to improve hepatocyte functions. Our HLCs might be promising for clinical cell transplantation to treat metabolic disease. Abstract : Highlight Saito and colleagues established a new three‐dimensional culture system for hepatocyte‐like cells generated from human adipose‐derived mesenchymal stem cells. 3D‐cultured hepatocyte‐like cells had higher albumin expression, CYP3A4 activity, urea synthesis, and ammonium metabolism than conventional 2D‐cultured hepatocyte‐like cells, suggesting their potential for clinical cell transplantation to treat metabolic liver disease.